Molecular characterization of antithrombin III (ATIII) variants using polymerase chain reaction. Identification of the ATIII Charleville as an Ala 384 Pro mutation. - Molho-Sabatier, P (1989)
The genes of seven structural mutants of antithrombin III (ATIII), presenting either defective serine protease reactivity or abnormal heparin binding, were analyzed. The polymerase chain reaction (PCR) was used to amplify the corresponding gene exon and the mutation was identified by either dot blot analysis using a battery of allele-specific oligonucleotide probes or sequencing. Variants Paris and Paris 2 were identified as Arg 47 Cys mutations, and Clichy, Clichy 2, and Franconville were found to be Pro 41 Leu mutations. All five are heparin binding-site variants. ATIII Avranches is an Arg 393 His mutation and ATIII Charleville is an Ala 384 Pro mutation. These two mutations impair the reactive site of the molecule. ATIII Charleville is a new mutation of the reactive center, as predicted by previous biochemical data. The position of this new mutation, together with the other previously described mutations of the reactive center, sheds light on the molecular function of this site in inhibiting thrombin. Finally, genomic amplification by PCR is a powerful technique for the fast identification of antithrombin III mutations and their homozygous/heterozygous status, and should be useful for predicting thrombotic risk.